PENGARUH CLIENT IMPORTANCE, AUDIT TENURE, DAN REPUTASI KANTOR AKUNTAN PUBLIK TERHADAP KUALITAS AUDIT - Chintary Putri Khoiriyah (2020)
This research is using quantitative study aimed to examine the effect of client importance is measured by Ln total asset method, audit tenure measured by the length of engagement between the client and public accounting firm, and reputation of public accounting firm is measured from the big four public accounting firm and non big four public accounting firm on audit quality. The population in this study is a property & real estate company listed on the Indonesia Stock Exchange in 2015-2018. The sample in this study amounted to 41 property & real estate companies found on the Indonesia Stock Exchange and the website of each company for the period 2015-2018 which were selected using the purposive sampling method. Hypothesis testing in this study was used Logistik Regression Analysis using SPSS analysis tool with a significant level of 5%. The result of hypothesis testing showed that (1) client importance had significant effect on audit quality (2) audit tenure had significant effect on audit quality (3) reputation of public accounting firm had no significant effect on audit quality.